Effect of bacteriocin from Lactobacillus sp. Var. SCG 1223 on microbiological quality of fresh meat - Usmiati, Sri; ., Miskiyah; R.A.M., Rarah (Indonesian Journal of Animal and Veterinary Sciences, 2009)
Inhibition technology of microorganism on meat can be done biologically and chemically. Biologically, inhibition to microbe can be conducted by addition antimicrobe, for example bacteriocin that have character as biopreservative. The aim of this research was to study the microbiological quality of fresh meat with bacteriocin isolated from Lactobacillus sp. SCG 1223 storaged at certain addition and temperature with different storage time. This experiment was done based on Completely of Random Design (CRD) with factorial arragement 3 x 4 for meat kept at room temperature (270C) and 3x3 for meat kept at cold temperature (4ÂºC) in three replications. The first factor was addition of biopreservative: addition bacteriocin (B), without addition antimicrobia (TB), and addition of nisin (N) on fresh meat. The second factor was different storage time at room temperature (H0, H6, H12 and H18) and low temperature (D0, D14, D28). Other treatments as indicators was contaminated with indicator bacteria (S. thypimurium, E. coli, L. monocytogenes). Variable analyzed were initial TPC (Total Plate Count) and total indicator bacteria S. thypimurium; E. coli; L. monocytogenes at fresh meat, meat quality consist of total indicator of bacteria, pH value of meat; and protein level. Result indicated that bacteriocin from Lactobacillus sp. SCG 1223 isolat could inhibit bacteria growth (S. thypimurium, L. monocytogenes, and E. coli. Bacteriocin produced by Lactobacillus sp. can work at room temperature (270C) and cold temperature (40C). Nisin effectivity almost same to bacteriosin produced from Lactobacillus sp. SCG 1223 isolated from cow fresh milk in inhibiting Gram positive L. monocytogenes. Key Words: Microbiological, Bacteriocin, Lactobacillus sp. Var. SCG 1223